Parental leave under scrutiny: is there substance over form? (European journal of volunteering and community-based projects, 2025)
Purpose. The purpose of this research is to examine how Italian listed companies on the FTSE MIB 40 disclose parental leave policies and employee well-being initiatives in their sustainability reports, with a focus on the reporting years 2017 and 2024. By investigating the extent and nature of such disclosures, the study aims to highlight whether and how firms integrate family-related policies into the broader social pillar of sustainability, thereby contributing to corporate accountability and transparency.Design/methodology/approach. A longitudinal content analysis was conducted on non-financial reports from FTSE MIB 40 companies for the years 2017 and 2024. The study combined quantitative frequency counts and qualitative assessments to evaluate disclosure practices on parental leave, employee well-being, and gender equality.Findings. The study shows that disclosures on parental leave and family-support policies have increased between 2017 and 2024, with more companies referencing paternity and aligning with SDG 5. Overall, while transparency and attention to social sustainability have improved, significant gaps persist in the depth, comparability, and substantive integration of parental leave policies within ESG reporting.Research implications. The study underscores the underdeveloped state of parental leave disclosure in corporate sustainability reporting and stresses the importance of further research into how companies communicate social sustainability practices. It contributes to the literature by bridging regulatory developments, stakeholder expectations, and corporate accountability in the context of employee well-being.Practical implications. For managers and policymakers, the findings highlight the need to strengthen parental leave policies and ensure their transparent disclosure within ESG frameworks. Firms are encouraged to embed family-support measures into broader people-care strategies, while regulators should promote standardized, comparable reporting that links commitments to measurable outcomes.Social implications. Strengthening the disclosure of parental leave policies can promote gender equality, support employee well-being, and foster inclusive workplaces. Greater transparency in this area contributes to reducing structural inequalities and advancing progress toward the Sustainable Development Goals.Originality/value. This study is among the first to examine parental leave disclosure within sustainability reports of Italian listed companies, comparing practices before and after recent EU regulatory reforms. By focusing on the social pillar of ESG, it adds novel insights into Corporate Family Responsibility and highlights how firms integrate (or neglect) employee well-being in their reporting.